Dried fish provide widespread access to critical nutrients across Africa - James P. W. Robinson; Lydia O’Meara; Kathryn J. Fiorella; Kendra A. Byrd; Marian Kjellevold; Richard S. Ansong; Christopher Mulanda Aura; Naftaly Mwirigi; Antonio Allegretti; Rucha Karkarey; Tim A. C. Lamont; Eva Maire; et al. (Proceedings of the National Academy of Sciences, 2025)
Aquatic foods are essential in supporting food security and nutrition across the tropics, with “dried” fish particularly affordable, available, and nutritious. However, dried fish food systems are often hidden and overlooked due to data scarcity, limiting understanding of how dried fish contribute to nutrient intakes. Here, we combine nutrient analysis of fish samples with national household surveys from across East and West Africa to understand the importance of dried fish in diets. We find that small portions of dried fish contribute over 15% of recommended intakes for multiple essential dietary nutrients (calcium, iodine, iron, selenium, zinc, and vitamins B12 and D), with low heavy metal concentrations, and are consumed weekly by ~one-third of households in six countries (Côte d’Ivoire, Nigeria, Malawi, Senegal, Tanzania, and Uganda) (~144 million people). Dried fish consumption was more prevalent than fresh fish, reaching 54% more people, particularly those in poor households and near to marine coastlines or urban centers. The widespread prevalence of nutritious dried fish suggests that these foods and their distribution networks play critical roles in food security and nutrition, even in households distant from fisheries or urban centers. Dried fish can fill nutrient gaps across the tropics but will require policies that mitigate negative effects of overfishing, environmental changes, and competition with international markets, while providing postharvest support to fish processors.